Radon concentration changes in ground water prior all the earthquakes (M>2.5) occurred from September 1998 to January 1999, in the area of Atalanti fault (Greece) - ΜΗΤΡΟΠΟΥΛΟΣ, Π.; NOTSU, Κ.; IGARASHl, G.; MORI, Τ.; ΔΕΛΗΜΠΑΣΗΣ, Ν.; ΚΑΚΚΑΒΑΣ, Ν. (Bulletin of the Geological Society of Greece, 2001)
Significant precursory changes in the radon concentration of groundwater were observed, 5-6 days prior all the earthquakes (M>2.5) occurred in the area of the Atalanti fault during the period from 22/9/1998-17/1/1999. The radon concentration measurements of ground water,were obtained at one hour intervals by the use of a ZnS(Ag) scintillation chamber. When no earthquake occurs, the radon concentration of the groundwater shows considerable stability. Prior of an earthquake radon concentration increases significantly at the beginning and then dropped to an also significant lower value. These radon concentration changes can be attributed to the temporary enrichment of the groundwater by radon from the surrounding rocks due to the action of stress release or stress accumulation prior an earthquake. It seems likely that the method can be an important tool for the earthquake prediction in local scale.